THE EFFECTIVENESS OF BALI TOURISM PROMOTION THROUGH OUT DIGITAL MARKETING VIDEOS - Herry Arianto,; I Gede Pitana,; Agung Suryawan Wiranatha,; Made Budiarsa, (International Journal of Social Science, 2022)
The advances in science and technology have also influenced the development of Bali tourism promotion strategies. In digital era 4.0, social media platforms and video-forming elements that can arouse consumers' emotions and desire to visit must be considered, so that messages and promotional objectives can be conveyed properly to consumers. This study aimed at analyzing the potential of Bali tourism promotion through digital video marketing so that it can be used as a strategy that is suitable for the current digital era.This research using qualitative and quantitative methods (mixed methods) in which the data were collected through interviews and questionnaires. The effectiveness of the video was calculated using CRI (Customer Response Index) by implementing AISAS concept. Incidental quota sampling was done to determine the research sample. The research was done on Facebook. The collected data were analyzed using digital marketing theories, AISAS, and the theories of tourism promotional video. The results showed that the five among six selected videos were uploaded to Facebook are considered effective in conveying the promotional messages. There was a video with a high value of CRI AIS in which it will directly affect the videos' virality because of the high numbers of shares. The videos' virality will boost the videos' popularity that has a significant relationship to the destination's popularity. A popular video is powerful enough to arouse the desire of consumers to visit a destination. This study found a relationship between the CRI AIS value with the level of motivation and consumer desire to visit. The higher the CRI AIS value, the higher the level of motivation to visit.